2009
DOI: 10.1016/j.jallcom.2008.02.057
|View full text |Cite
|
Sign up to set email alerts
|

Phase relations and flux research for zinc oxide crystal growth in the ZnO–K2O–P2O5 system

Abstract: a b s t r a c tThe subsolidus phase relations of the ternary system ZnO-K 2 O-P 2 O 5 were investigated by means of Xray diffraction (XRD). There are 7 binary compounds, 6 ternary compounds and 20 three-phase regions in this system. The phase diagram of the pseudo-binary system KZn 4 (PO 4 ) 3 -ZnO was also investigated by means of XRD and differential thermal analysis (DTA) methods. KZn 4 (PO 4 ) 3 -ZnO is a eutectic system with eutectic temperature about 952 • C and eutectic point at about 2 mol% ZnO. Only n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…In the ZnO-Li 2 O system, no compound was synthesized under our experimental conditions, similar to the ZnO-Na 2 O [7] and ZnO-K 2 O systems [8].…”
Section: Binary Systemsmentioning
confidence: 99%
“…In the ZnO-Li 2 O system, no compound was synthesized under our experimental conditions, similar to the ZnO-Na 2 O [7] and ZnO-K 2 O systems [8].…”
Section: Binary Systemsmentioning
confidence: 99%
“…Since the melting point of P 2 O 5 is relatively low at about 580 °C, it is useful to study phase relations of the ternary system ZnO– A 2 O( A =Li,Na,K)–P 2 O 5 and to explore a suitable flux for the growth of ZnO crystals. During our study of phase relations and flux research for zinc oxide crystal growth in the ZnO–K 2 O–P 2 O 5 system (Ji et al , 2008), we found the existence of the compound K 2 Zn(PO 3 ) 4 . Since the melting point of K 2 Zn(PO 3 ) 4 is 625 °C, the compound is a promising ternary compound to be used as a flux.…”
Section: Introductionmentioning
confidence: 84%
“…P 2 O 5 has low melting point (580 • C) and mixture of P 2 O 5 /V 2 O 5 has been used for flux growth of ZnO crystal by Wanklyn in 1970 [19]. Recently, Ji et al [20][21][22][23] have investigated the subsolidus phase relations of ternary systems ZnO-P 2 O 5 -A 2 O (A = Li, Na, K) and ZnO-P 2 O 5 -B 2 O 3 . Hong et al [24] also studied the ternary system ZnO-P 2 O 5 -MoO 3 .…”
Section: Introductionmentioning
confidence: 99%